Fast light-induced reversible wettability of a zinc oxide nanorod array coated with a thin gold layer. (4th October 2017) - Wei, Yuefan; Du, Hejun; Kong, Junhua; Tran, Van-Thai; Kai Koh, Jia; Zhao, Chenyang; He, Chaobin
Abstract: Zinc oxide (ZnO) has gained much attention recently due to its excellent physical and chemical properties, and has been extensively studied in energy harvesting applications such as photovoltaic and piezoelectric devices. In recent years, its reversible wettability has also attracted increasing interest. The wettability of ZnO nanostructures with various morphologies has been studied. However, to the best of our knowledge, there is still a lack of investigations on further modifications on ZnO to provide more benefits than pristine ZnO. Comprehensive studies on the reversible wettability are still needed. In this study, a ZnO nanorod array was prepared via a hydrothermal process and subsequently coated with thin gold layers with varied thickness. The morphologies and structures, optical properties and wettability were investigated. It is revealed that the ZnO–Au system possesses recoverable wettability upon switching between visible–ultraviolet light and a dark environment, which is verified by the contact angle change. The introduction of the thin gold layer to the ZnO nanorod array effectively increases the recovery rate of the wettability. The improvements are attributed to the hierarchical structures, which are formed by depositing thin gold layers onto the ZnO nanorod array, the visible light sensitivity due to the plasmonic effect of the deposited gold, as well as the fast charge-induced surface status change upon light illumination or dark storage. The improvement is beneficial to applications in environmental purification, energy harvesting, micro-lenses, and smart devices.